2016
DOI: 10.1638/2014-0134.1
|View full text |Cite
|
Sign up to set email alerts
|

RETROSPECTIVE REVIEW OF MORTALITY IN GIANT PACIFIC OCTOPUS (ENTEROCTOPUS DOFLEINI)

Abstract: The giant Pacific octopus (Enteroctopus dofleini) is a popular exhibit species in public display aquaria, but information on health and disease is limited. This retrospective review evaluates time in collection and describes antemortem clinical signs and pathology of giant Pacific octopuses in an aquarium setting. Between March 2004 and December 2013, there were 19 mortalities: eight males, 10 females, and one individual whose sex was not recorded. Average time spent in collection for all octopuses was 375 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…This study is the first of its kind to have facilities holding E. dofleini document extensive health and welfare assessments, general observations and husbandry practices over an extended period of time. While other studies have used records to retrospectively assess the health of E. dofleini (Seeley et al, 2016), none have documented health changes in real time among multiple facilities. While it is not surprising to most E. dofleini caretakers that changes in feeding behavior and response to stimulus would indicate terminal decline and senescence (Anderson et al, 2002), this is the first study to document a timeline of these behavioral changes associated with senescence and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first of its kind to have facilities holding E. dofleini document extensive health and welfare assessments, general observations and husbandry practices over an extended period of time. While other studies have used records to retrospectively assess the health of E. dofleini (Seeley et al, 2016), none have documented health changes in real time among multiple facilities. While it is not surprising to most E. dofleini caretakers that changes in feeding behavior and response to stimulus would indicate terminal decline and senescence (Anderson et al, 2002), this is the first study to document a timeline of these behavioral changes associated with senescence and death.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot conclude from this study if cephalopods may suffer or experience pain in the same sense that vertebrates do, it is certainly reasonable to assume that injury can compromise the welfare of cephalopods. Even a minor injury can be reflected in morbidity and mortality, such as small fin or mantle abrasions (Hulet, Villoch, Hixon, & Hanlon, 1979;Seeley et al, 2016) and associated bacterial infections (Sherrill, Spelman, Reidel, & Montali, 2000). Therefore, any exposure to injury would implicate a change in the animal's welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in cephalopod models in research is growing (Fiorito et al, 2015) and cephalopods continue to be popular display animals in aquariums, inspiring visitors with their unique anatomy, color changing capabilities and intelligence (Seeley et al, 2016). Most cephalopods are semelparous, meaning they experience a single, terminal reproductive event followed by a period of senescence (Rocha et al, 2001), which is characterized by various behavioral and physiological changes including anorexia, major deterioration of the skin and muscle, sinking of the eyes, stereotypic repetitive behaviors and, occasionally, self-mutilation and autophagy (Anderson et al, 2002;Holst & Miller-Morgan, 2020;Roumbedakis et al, 2018; Z.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the scientific literature documenting spontaneous diseases of cephalopods, particularly in aquaria, is scattered and poorly reviewed with only limited scale retrospective studies having been recorded to date. 26,76,77 This study describes spontaneous disease identified 1186306V ETXXX10.…”
mentioning
confidence: 99%